2020
DOI: 10.1007/s12520-020-01016-2
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric and historical insights in avian zooarchaeology, taphonomy and ancient bird use

Abstract: and Argentina gathered to present findings and participate in birding events. The Lower Rio Grande Valley (Starr, Hidalgo, Cameron and Willacy counties) provides habitat supporting about 520 resident, migratory and rare bird species, almost half of the 1114 recorded occurring in the USA as a whole. The presence of many tropical bird species encourages birders to visit in large numbers. Regional ecotourism that includes birding generated (as of ca. 2010) more than $300 million in local yearly revenue (Woosnam e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
8
0
2
Order By: Relevance
“…Los resultados del análisis tafonómico mostraron también una importante fragmentación del conjunto y la incidencia de raíces y carbonato, cuyos efectos son frecuentes en conjuntos arqueofaunísticos del valle medio del río Negro (Mange et al, 2016;Mange et al, 2020). Esta elevada fragmentación, ocurrida fundamentalmente cuando los huesos estaban en estado seco, se relacionaría con la fragilidad intrínseca de los huesos de aves (Dirrigl et al, 2020), con la abundante incidencia de termoalteración, con la actividad radicular de los arbustos que cubren este sector del valle y con la acción de animales fosoriales (roedores y eufractinos). La presencia de marcas de raíces, el predominio de estadios bajos o ausencia de meteorización en la muestra de mamíferos y la escasez de especímenes 2008; Mange et al, 2016;Mange, 2019) contrasta con las numerosas referencias históricas que consideraron a estas aves como el alimento preferido por los pueblos indígenas norpatagónicos (Casamiquela, 1985;Salemme y Frontini, 2011).…”
Section: Discussionunclassified
“…Los resultados del análisis tafonómico mostraron también una importante fragmentación del conjunto y la incidencia de raíces y carbonato, cuyos efectos son frecuentes en conjuntos arqueofaunísticos del valle medio del río Negro (Mange et al, 2016;Mange et al, 2020). Esta elevada fragmentación, ocurrida fundamentalmente cuando los huesos estaban en estado seco, se relacionaría con la fragilidad intrínseca de los huesos de aves (Dirrigl et al, 2020), con la abundante incidencia de termoalteración, con la actividad radicular de los arbustos que cubren este sector del valle y con la acción de animales fosoriales (roedores y eufractinos). La presencia de marcas de raíces, el predominio de estadios bajos o ausencia de meteorización en la muestra de mamíferos y la escasez de especímenes 2008; Mange et al, 2016;Mange, 2019) contrasta con las numerosas referencias históricas que consideraron a estas aves como el alimento preferido por los pueblos indígenas norpatagónicos (Casamiquela, 1985;Salemme y Frontini, 2011).…”
Section: Discussionunclassified
“…On the other hand, it must be emphasized that different archaeological sites have yielded very different results with regard to the relative number of avian bone elements (cf. Dirrigl et al, 2020), which in principle leaves room for alternative interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Birds played an important role in the ancient economy and culture. The study of avifaunal remains can provide valuable insights into a variety of topics, including palaeo‐diet, consumption patterns, tool making, cultural symbols, art and iconography, feather ornamentation, ethnology, medicine, musical instruments and palaeoenvironmental reconstruction (Dirrigl et al, 2020 and references therein). Despite its potential, avian archaeozoology has rarely been studied in the south‐eastern Alpine region (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Both the utilitarian and symbolic significance of birds to the people of the Late Neolithic must be considered. Ethnographic studies have shown that birds have almost always had a symbolic role among human societies (Dirrigl et al 2020;Serjeantson 1997). All over the world people have used feathers for decoration, display and social signalling.…”
Section: Culturementioning
confidence: 99%